2020
DOI: 10.1002/ar.24407
|View full text |Cite
|
Sign up to set email alerts
|

A 60:40 split: Differential mass support in dogs

Abstract: Dogs have been bred for different sizes and functions, which can affect their locomotor biomechanics. As quadrupeds, dogs must distribute their mass between fore and hind legs when standing. The mass distribution in dogs was studied to determine if the proportion of supported mass on each limb couplet is dependent on body size. A total of 552 dogs from 123 breeds ranging in size from Chihuahua to Mastiff were examined. Each dog was weighed on a digital scale while standing, alternating foreleg, and hind leg su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…During quadrupedal locomotion, peak vertical substrate reaction forces are almost universally greater within the forelimb than in the hindlimb across mammals (Barclay, 1953; Fish et al, 2021; Jayes & Alexander, 1978; Kimura & Endo, 1972; Reynolds, 1985a). An exception to this pattern, however, is the Order Primates, wherein this pattern is switched (Demes et al, 1994; Kimura et al, 1977; Reynolds, 1985b).…”
Section: Introductionmentioning
confidence: 99%
“…During quadrupedal locomotion, peak vertical substrate reaction forces are almost universally greater within the forelimb than in the hindlimb across mammals (Barclay, 1953; Fish et al, 2021; Jayes & Alexander, 1978; Kimura & Endo, 1972; Reynolds, 1985a). An exception to this pattern, however, is the Order Primates, wherein this pattern is switched (Demes et al, 1994; Kimura et al, 1977; Reynolds, 1985b).…”
Section: Introductionmentioning
confidence: 99%
“…The mean body weight distribution between fore-and hindlimbs is approximately 60% : 40% in dogs [56,94]. A large study investigating 123 different breeds found that the grand mean proportion of mass was 60.4% on the forelimbs (range: 47.6 to 74.4%) [94]. Only sex was shown to be a significant factor altering that ratio, with females being below the mean value throughout different breeds [94].…”
Section: Joint Contact Areas and Force Distribution Within The Elbow Jointmentioning
confidence: 99%
“…The mean body weight distribution between fore-and hindlimbs is approximately 60% : 40% in dogs [56,94]. A large study investigating 123 different breeds found that the grand mean proportion of mass was 60.4% on the forelimbs (range: 47.6 to 74.4%) [94].…”
Section: Joint Contact Areas and Force Distribution Within The Elbow Jointmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial selection has resulted in a plethora of dog body shapes, ranging from short‐legged to long‐legged, gracile to stocky, as a result of breeding for speed, strength, or aesthetics. Despite the variety, Fish et al (Fish, DiNenno, & Trail, 2021a; Fish, Sheehan, Adams, Tennett, & Gough, 2021b) find remarkable homogeneity in two aspects of dog locomotor anatomy, how they distribute their mass over their limbs and how they swim (“dog‐paddle”). His study of 552 dogs across 123 breeds, spanning the 2.7 kg chihuahua to the 104 kg mastiff, found that all breeds exhibit an ~60:40 split in distribution between mass on their forelimbs and hindlimbs.…”
Section: Living Near Wolves Walking With Dogsmentioning
confidence: 99%